Curcumin, demethoxycurcumin, and bisdemethoxycurcumin induced caspase-dependent and -independent apoptosis via Smad or Akt signaling pathways in HOS cells - Cheng Huang; Hsu-Feng Lu; Yu-Hsuan Chen; Jui-Chieh Chen; Wen-Hsiang Chou; Hsiu-Chen Huang (BMC, 2020)
Abstract Background Osteosarcoma is the most common primary malignant bone tumor in children and adolescents and has also been associated with a high degree of malignancy and enhanced metastatic capacity. Curcumin (CUR) is well known for its anti-osteosarcoma activity. However, both demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC) are natural curcumin analogues/congeners from turmeric whose role in osteosarcoma development remains unknown. Methods To evaluate the growth inhibitory effects of CUR, DMC and BDMC on osteosarcoma (HOS and U2OS), breast (MDA-MB-231), and melanoma (A2058) cancer cells, we employed the MTT assay, annexin V-FITC /7-AAD staining, and clonogenic assay. Results CUR,DMC, and BDMC all decreased the viability of HOS, U2OS, MDA-MB-231, and A2058 cancer cells. Additionally, CUR,DMC, and BDMC induced the apoptosis of HOS cells through activation of Smad 2/3 or repression of Akt signaling pathway. Furthermore, the combination of CUR,DMC, and BDMC synergistically reduced cell viability, colony formation and increased apoptosis than either two or a single agent in HOS cells. Conclusions The combination of these three compounds could be used as a novel target for the treatment of osteosarcoma.